Developing Project-Based Writing Assessment Module to Stimulate Students’ Critical Thinking and Creativity - Lestari, Tutik; Bharati, Dwi Anggani Linggar; Rukmini, Dwi (English Education Journal, 2018)
This study aimed at developing project–based writing assessment module to stimulate the students’ critical thinking and creativity since most of teachers get difficulty in developing a higher-order thinking assessment.This study used Research and Development where the subject of this study was the students of X IPS 2 of SMAN 12 Semarang in the academic year of 2017/2018. Questionnaire, interview, observation checklist, and test were used as the instrument in collecting the data. The teacher collaborated with the researcher in developing the project-based writing assessment module. After the module was revised based on the experts’ suggestions, the main field testing was conducted. The module was utilized during the treatments.The students’ score improvement of the writing skill was 67.55 to 80.11, critical thinking skill was 67 to 78, and creativity skill was 65.39 to 78.55. Moreover, the paired sample test results show that there is significantly difference between the result of pre-test and post-test. In other words, there is a significant improvement in the students’ writing skill, critical thinking skill, and creativity skill after they used project-based writing assessment.